Effects of urea foliar application on growth and yield of green pepper - Gulab, Gulbuddin; Abdiani, Saidajan Attiq; Kakar, kifayatullah; Aryan, Shafiqullah (International Journal of Innovative Research and Scientific Studies, 2019)
Vegetable crops require nutrients in various quantities for growth, development, and reproduction. Plants nutrients might be naturally available from soil or/ and atmosphere. However, modern cultivation needs artificial supplementation of nutrients. Green pepper is an important vegetable crop in several countries including Afghanistan. Irregular rates and methods of fertilizers application in green pepper production caused its yield to decrease. A study was conducted at the experimental farm of agriculture faculty; Nangarhar University in 2017 with traditional method (control), 1%, 2% and 3% of urea foliar application treatments under the randomized complete block design, this study aimed to investigate and point out the best fertilizer application rate and method for green pepper production in Afghanistan, especially Nangarhar province. The control treatment increased plant height, fruit length, fruit weight, fruit yield and consequently net income compared to other treatments. However, 3% treatment had negligible differences with control; although 1% and 2% treatments got third and fourth positions, respectively. In 3% treatment, the urea was efficiently utilized with lower urea losses compared to the control treatment. Further researches should undertake to find out the proper application rates and methods for other chemical fertilizers.